(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This essay makes the case that in-depth analyses of national cultures must be added to the dimensional view on culture, which is likely the most significant advancement in cross-cultural understanding in the last 50 years. A cultural metaphor, defined as any action, occurrence, or institution that individuals of a certain culture emotionally and/or intellectually connect with, aims to alleviate such a condition. Hence, cultural metaphors serve as a reflection of a culture’s core beliefs.